Effect of probiotic-based vaccination on lactate availability in immune inductive tissues - Kiehl, Sophie, author; Kiehl, Paris M., author; Fletcher, McKenzie, author; Kinkel, Traci, committee member; Vilander, Allison, committee member; Dean, Gregg, advisor (Colorado State University. Libraries, 2025)
Lactic acid bacteria (LAB) colonize the gastrointestinal tract and generally confer immune benefits to their host. Because of this, they are emerging as viable vaccine vectors, particularly against mucosal pathogens. LAB secrete high quantities of lactate as a byproduct of their metabolism, and lactate has been increasingly recognized as an immunomodulator, often in an anti-inflammatory capacity. We are studying how lactate metabolism of LAB-based vaccines affects lactate availability in immune inductive sites using the bacterial platform Lactobacillus acidophilus. Using Mirasol® Pathogen Reduction Technology system, we inactivated a recombinant L. acidophilus expressing the model antigen ovalbumin. We first verified that inactivation inhibited bacterial growth and reduced lactate metabolism while preserving antigen expression. We then administered the live and inactivated vaccines orally to BALB/c mice and measured lactate concentrations in harvested immune inductive sites (Peyer's patches and ileal lumen contents) using gas chromatography mass spectrometry. Lactate levels in the ileum and Peyer's patches were unchanged following administration with probiotic-based vaccines, suggesting their administration does not disrupt the metabolic equilibrium of these tissues that may trigger an anti-inflammatory state.
Department of Microbiology, Immunology, and Pathology
Additional authors supplied by Sophie Kiehl.
Keywords: probiotic-based vaccine; lactate; Mirasol